2006
DOI: 10.1038/sj.mp.4001780
|View full text |Cite
|
Sign up to set email alerts
|

Family-based association study of Epsin 4 and Schizophrenia

Abstract: Recently, Pimm et al. identified Epsin 4 on chromosome 5q33 as a susceptibility gene for schizophrenia in the British population, based on linkage and association evidence. In Pimm's case-control study, both the single polymorphisms and the individual haplotypes at the 5 0 end of the gene showed genetic association with schizophrenia. Here, we report the first study evaluating the relevance of Epsin 4 and schizophrenia outside the British population. Markers showing positive results in the original work as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…18 Pimm et al 19 reported an association with the Epsin 4 gene found on 5q33.3, in a large case-control sample from the UK, and this gene was further implicated by a follow-up study on a Chinese sample that showed an association between Epsin 4 haplotypes and schizophrenia. 20 This gene is a schizophrenia candidate owing to its involvement with neurotransmitter vesicle transport and stability in the synapses and neurones. 19 Taken together, these studies provide strong evidence for schizophrenia susceptibility in the region in which we have confirmed an iUPD, a chromosomal abnormality that can be detrimental owing to the homozygosity of autosomal recessively inherited disorders and imprinting.…”
Section: Discussionmentioning
confidence: 99%
“…18 Pimm et al 19 reported an association with the Epsin 4 gene found on 5q33.3, in a large case-control sample from the UK, and this gene was further implicated by a follow-up study on a Chinese sample that showed an association between Epsin 4 haplotypes and schizophrenia. 20 This gene is a schizophrenia candidate owing to its involvement with neurotransmitter vesicle transport and stability in the synapses and neurones. 19 Taken together, these studies provide strong evidence for schizophrenia susceptibility in the region in which we have confirmed an iUPD, a chromosomal abnormality that can be detrimental owing to the homozygosity of autosomal recessively inherited disorders and imprinting.…”
Section: Discussionmentioning
confidence: 99%
“…In several of these loci association studies identified putative common susceptibility genes, such as DISC1 on chromosome 1q42, 13 FZD3 14 and NRG1 15 on 8p2, Epsin 4 17,18 and GABAA receptor 19 on chromosome 5q. In addition, a new gene, ST8SIA2 (also known as SIAT8B), which maps on chromosome 15q26, has been recently associated with SZ in a Japanese sample.…”
Section: Introductionmentioning
confidence: 99%
“…ADAM19 , which is directly pinpointed by the presence of an exonic SNP significantly linked to BP‐I (rs1422795, LOD = 4.1), is an interesting functional candidate due to its role in the proteolytic processing of neuregulin 1 [Yokozeki et al, 2007], which is a key element of the neuregulin‐erbB signaling pathway, putatively impaired in psychiatric diseases [Roy et al, 2007]. The second candidate gene, CLINT1 , is suggested as a candidate for vulnerability to psychopathology by its association with schizophrenia in UK, Chinese, and Latin American populations [Pimm et al, 2005; Liou et al, 2006; Tang et al, 2006; Gurling et al, 2007; Escamilla et al, 2008]. Epsin 4 which is a protein product of the CLINT1 gene was shown to be involved in endocytotic internalization, regulation of inositol phospholipid levels, membrane structure, and trafficking through direct binding to membrane clathrin and other associated proteins, such as AP‐1 and AP‐2 [McPherson and Ritter, 2005].…”
Section: Discussionmentioning
confidence: 99%